2010
DOI: 10.1021/ma100449n
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Geometry and Kinetics of Polymer Confined in Self-Assembly via Cooperative Hydrogen Bonding: A Solid-State NMR Study under Paramagnetic Doping

Abstract: Well-defined arrangements of the secondary intermolecular interactions play important roles for the design of new materials, which leads to unique self-assemblies consisting of multicomponent molecules with different sizes and shapes. Much work has gone into characterizing the static structures of such selfassembled systems. 1 Cooperative secondary interactions influence the molecular dynamics of the components and the bulk properties. Therefore, understanding relationship between microscopic dynamics and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“… For a -hPNB, the CODEX decaying curves get deeper and deeper with increasing temperature. Similar observations were reported in several mobile polymer crystals such as PEO, i -PP, , i -P4M1P, PLLA, and so forth. For i -hPNB, the CODEX t mix decaying curve for the C5,6 carbon of i -hPNB initially follows a similar trend with a -hPNB.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“… For a -hPNB, the CODEX decaying curves get deeper and deeper with increasing temperature. Similar observations were reported in several mobile polymer crystals such as PEO, i -PP, , i -P4M1P, PLLA, and so forth. For i -hPNB, the CODEX t mix decaying curve for the C5,6 carbon of i -hPNB initially follows a similar trend with a -hPNB.…”
Section: Resultssupporting
confidence: 88%
“…This implies that the cyclopentyl ring is not limited to two conformations but is flexible and adopts multiple conformations. The characteristic reorientation angles of 5–30° in a -hPNB are quite unique compared to those of other mobile crystals such as PE, i -PP, , PEO, i -P4M1P, i -PB1 form III, PLLA, and so forth, which achieve high reorientation angles (75–200°) depending on their conformations. Register and co-workers investigated crystal unit-cell parameters of a -hPNB below T cc and reported the 0.5% contraction of the c -axis dimension between 23 and 95 °C .…”
Section: Resultsmentioning
confidence: 96%
“…In this work, molecular dynamics of the PLA chains in the α′, SC, and glassy samples in a slow dynamic regime for correlation time, 〈τ c 〉, of 10 −3 to 10 2 s are investigated by centerband‐only detection of exchange (CODEX) NMR . The evolution‐time dependence of the CODEX decay curve revealed that PLLA chains in the SC and α′ in addition to the α form exhibit large‐amplitude helical jump motions, similar to those previously observed for several polyolefins and other polymers . Moreover, the temperature dependence of the 〈τ c 〉 values, as determined by mixing‐time dependence CODEX experiments, indicated the kinetics of the molecular motions in three crystalline phases largely different from each other.…”
Section: Introductionsupporting
confidence: 64%
“…[35] The evolution-time dependence of the CODEX decay curve revealed that PLLA chains in the SC and α′ in addition to the α form [34] exhibit large-amplitude helical jump motions, similar to those previously observed for several polyolefins [4][5][6][7]9,14] and other polymers. [36,37] Moreover, the temperature dependence of the 〈τ c 〉 values, as determined by mixing-time dependence CODEX experiments, indicated the kinetics of the molecular motions in three crystalline phases largely different from each other. Comparisons of the reported crystalline structures and dynamic data obtained during the current study provide detailed information about the relationship between structure and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Dipolar-based ssNMR techniques have successfully revealed the three dimensional structure of peptides, as well as biomacromolecules, in the past decade [28,29,30]. In polymers, molecular motions including time scale and amplitude of re-orientations in the glassy [27], crystalline [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47], and melt [48,49] states, and local packing [50] and conformation [51] in the glassy state have been elucidated by various NMR techniques.…”
Section: Introductionmentioning
confidence: 99%